FEASIBILITY FINANCIAL ANALYSIS OF COMMERCIAL AREA INVESTMENT AT XYZ AIRPORT - Septiandy, Luthfi; Rahadi, Raden Aswin (Journal of Surveying, Construction and Property, 2020)
PT XYZ is enterprises that belong to West Java Provinces due to their status as regional owned enterprises. In May 2018 one of their unit XYZ Airport start the first flight to Surabaya. To increase enterprises growth, enterprises are necessary to determine the new revenue stream. The airport industry the revenue divided into two types of aero revenue and non-aero revenue. In this research focused on the non-aero sector, at the moment, XYZ has 12 Ha area that can utilize economically to investing. Based on best practice at the predecessor, the favorable investment that can be conducted in developing the commercial area surrounding the airport. The benchmark also shows that the commercial area consists of hotel facility, outlet, retail park, and another supporting facility. Through AHP analysis, the suitable business model that firm can adopt is Joint Venture Agreement (JV) with the highest weight 37,74% biggest among other business models Kerja Sama Pengusahaan and Build Operate Transfer. For the financial aspect, there three scenarios that differences based on the source of fund. The total investment that tenant needs in order to develop a commercial area is Rp. 491.302.150.000 otherwise for XYZ the investment is amount Rp. 188.647.712.794. From the analysis the Scenario 2 is favorable based on the result of feasibility with discounted payback period nine years, NPV amount Rp. 3.637.491.236.349. The profitability index also shows that investment is profitable over the requirement ( > 1,00) also the internal rate of return higher than cost of capital with 27,68 %. For sensitivity analysis, there four parameters as the basis to calculate, and the analysis shows interest rate with swing 10% from basis point resulting huge deviation from NPV -17,26%